20% by 2020? Economy-wide impacts of energy efficiency improvement in Germany - Ulrike Lehr; Christian Lutz; Martin Pehnt; Udo Lambrecht; Friedrich Seefeldt; Marco Wünsch; Barbara Schlomann; Tobias Fleiter (Gesellschaft für Wirtschaftliche Strukturforschung (GWS), 2011)
The paper presents results of the implementation of an efficiency strategy in Germany until 2020 which is focused on cost-effective measures. The efficiency measures are calculated in bottom-up models and translated into a top-down macro-economic model. The comparison to a business as usual simulation shows some economy-wide rebound effects of about 17% of the overall energy savings. The analysis is limited to 2020. Given that an efficiency strategy is a long-term strategy, this puts the results on the rather conservative side. The results clearly show that improved energy efficiency results in a variety of positive effects on the economy and the environment. These range from reduced greenhouse gas emissions to improved competitiveness of firms and budget savings for consumers to economy wide impacts like additional employment and economic growth. Even the consideration of rebound effects did not change this picture significantly. Thus, exploiting the huge potential stemming from cost-effective efficiency measures should have high priority for the design of energy and climate policies.
Keywords: Q43; 330; energy efficiency; bottom up scenario analysis; climate policy; Energieeinsparung; Makroökonomischer Einfluss; Deutschland